Comparison of Oral Microbe Quantities from Tongue Samples and Subgingival Pockets - André Göhler; Stefanie Samietz; Carsten Oliver Schmidt; Thomas Kocher; Ivo Steinmetz; Birte Holtfreter (International Journal of Dentistry)
Objectives. To improve understanding of periodontitis pathology, we need more profound knowledge of relative abundances of single prokaryotic species and colonization dynamics between habitats. Thus, we quantified oral microbes from two oral habitats to gain insights into colonization variability and correlation to the clinical periodontal status. Methods. We analyzed tongue scrapings and subgingival pocket samples from 237 subjects (35–54 years) with at least 10 teeth and no recent periodontal treatment from the 11-year follow-up of the Study of Health in Pomerania. Relative abundances of Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, Streptococcus sanguinis, total bacteria, and Archaea were correlated to clinically assessed pocket depths (PD) and clinical attachment levels (CAL). Results. Increased relative abundances of P. gingivalis, A. actinomycetemcomitans, and F. nucleatum were linked to increased levels of PD and CAL (i) on the subject level (mean PD, mean CAL) and (ii) in subgingival pockets. Relative abundances of Archaea from tongue samples correlated negatively with mean PD or mean CAL. Detection and quantity of bacterial species correlated weakly to moderately between the tongue and subgingival pocket, except for Archaea. Conclusions. Relative abundances of specific oral species correlated weakly to moderately between habitats. Single species, total bacteria, and Archaea were linked to clinically assessed severity of periodontitis in a habitat-dependent manner.